Biodegradation of vegetable residues by polygalacturonase-agar using a trickle-bed bioreactor - Ramírez Tapias, Yuly Andrea (2018)
Bacterial pectinases degrade the pectic substances present in plant tissues and particularly, polygalacturonases catalyze the hydrolysis of α-(1,4) glycosidic bonds linking D-galacturonic acid units. In this study, polygalacturonase from Streptomyces halstedii ATCC 10897 was immobilized by the matrix entrapment technique using different thermogels. Bacteriological agar added with magnesium cation produced beads with a more stabilized microstructure for enzyme retention, monitored by oscillatory measurements of storage and loss modulus. Agar concentration and protein content were optimized to maximize protein entrapment, product conversion, and reaction yield. Results showed that the mixture at 10:90% (v/v) of protein (2 mg/mL) and agar (4% w/v) was the best immobilization condition to retain 91% of protein and hydrolyze 38% of pectin to allow the highest reaction yield (9.279 g/g) and increase stability up to 48 h of successive reactions. Agarose bead biocatalysts were used in a trickle-bed column operated with recirculation, and this bioreactor allowed the degradation of pear and cucumber residues by enzymatic liquefaction to enhance sugar content up to 15.33 and 9.35 mg/mL, respectively, and decrease viscosity by 92.3%. The scale-up of this process adds value to vegetable residues such as fructooligosaccharides or fermentable sugars, which become a sustainable source of fuels and chemicals.